Initial Development and Psychometric Validation of the Self-Efficacy Scale for Informational Reading Strategies in Teacher Candidates - Goktenturk, Talha; Omay, Yigit; Arici, Ali Fuat; Yazici, Emre; Ozbasi, Sevgen (MDPI, 2025)
Assessing teacher candidates' self-efficacy in using reading strategies is essential for understanding their academic development. This study developed and validated the Teacher Candidates' Self-Efficacy Scale for Informational Reading Strategies (TCSES-IRS) using a mixed-methods sequential exploratory design. Initial qualitative data from interviews with 33 candidates and a literature review guided item generation. Lawshe's method confirmed content validity. The scale was administered to 1176 teacher candidates. Exploratory (n = 496) and confirmatory factor analyses (n = 388) supported a five-factor structure-cognitive, note-taking, exploration and preparation, physical and process-based, and reflective and analytical strategies-explaining 63.71% of total variance, with acceptable fit indices (chi 2/df = 2.64, CFI = 0.912, TLI = 0.900, RMSEA = 0.069). Internal consistency was high (alpha = 0.899 total; subscales alpha = 0.708-0.906). An additional sample of 294 participants was used for nomological network validation. Convergent validity was demonstrated by significant item-total correlations and strong factor loadings. Discriminant validity was evidenced by moderate inter-factor correlations. Criterion-related validity was confirmed via significant group differences and meaningful correlations with an external self-efficacy measure. The TCSES-IRS emerges as a psychometrically sound tool for assessing informational reading self-efficacy, supporting research and practice in educational psychology.
Keywords: informal reading strategies; self-efficacy; scale development; teacher candidates; educational psychology; EXPLORATORY FACTOR-ANALYSIS; STUDENTS; OUTCOMES; SKILLS; Psychology